Social Representation Theory meets Cultural Studies in Indonesia: Seeking new possibilities to accommodate emerging studies on culture - Permanadeli , Risa (Revista Educação e Cultura Contemporânea, 2024)
Knowledge production is always contextualized according to local culture. This article discusses emerging studies on culture in Indonesia in the late 20th century, connected to national history. It highlights a movement against the previous trend of adopting Western approaches in the name of modernization, ignoring culture and history. The article emphasizes Social Representations Theory and Cultural Studies, emphasizing how representations contribute to identity formation and shape social perceptions. It explores the interconnection of these approaches and the need for a methodological strategy adapted to cultural and historical context.